A Survey on Various Forwarding Protocols Scheme for Named Data Network in MANET - Priya, P. Lakshmi; Premkumar, K (International Journal of Computer Sciences and Engineering, 2025)
In this work, the Provider aware forwarding convention is planned as illustrative of the attentive distribution classification. The considered arrangement is planned not to modify the Interest/Data trade and without extra packages. The main required information structure is the alleged Distance Table, which keeps up panel of data between every centre and the correspondence endpoints. LFBL use three packet type content demand and reply, which are utilized like Interest and Data bundles, and acknowledgement, which is utilized by the consumer to affirm the provider determination. The information healing happens by steps: first, the Interest is scattered in the system with a controlled flooding procedure so as to find the accessible provider; at that point, the consumer chooses a provider and sends an acknowledgement packet for assertion; at long last, a separation based sending plan is empowered, so each middle of the path centre chooses if sending the resulting content demand or not by checking its Distance table. In particulars every core keeps up the Distance table, in addition to the standard NDN table, which incorporates, for each prepared content name, the provider identifier (ID) and the bound partition to it